Healthcare-seeking behavior among ill children under five in Bangladesh: a multinomial analysis - Haque, Shahnaz; Mohd, Saidatulakmal (Universiti Teknologi MARA Selangor, 2025)
Bangladesh has a complex healthcare system. Despite improvements in healthcare infrastructure, a significant proportion of children under five with illnesses are still taken to unqualified healthcare providers, or their parents rely on pharmacies, traditional healers, or self-care for treatment. However, expanding access to substandard care is unlikely to improve health outcomes. This study aims to analyze the demographic and socioeconomic factors influencing healthcare-seeking behavior (HSB) using nationally representative data from the Bangladesh Household Income and Expenditure Survey (2016). Guided by Andersen's behavioral model of health services use, a multinomial logistic regression model is applied to identify factors affecting HSB. The findings reveal that variables such as the mother's age, urban residence, household wealth index, and the presence of multiple illnesses increase the likelihood of seeking care from qualified healthcare providers. In contrast, no significant association is found between the child's sex and parental healthcare-seeking behavior. Additionally, as children grow older, parents are more likely to turn to pharmacies, traditional healers, or self-care options. The analysis also shows that while children of educated mothers are more likely to receive care from qualified providers, those whose mothers are employed are more often treated through pharmacy/traditional/self-care methods. Further research is needed to explore the underlying reasons for this behavior among working mothers. Policymakers should prioritize reducing rural-urban disparities and poverty. Moreover, increasing public awareness about the importance of addressing childhood illnesses through nationwide workshops or seminars can help prevent neglect and mistreatment.